2020
DOI: 10.1002/ps.6013
|View full text |Cite
|
Sign up to set email alerts
|

Host searching and host preference of resident pupal parasitoids of Drosophila suzukii in the invaded regions

Abstract: BACKGROUND: In its invaded regions, Drosophila suzukii (Matsumura) is a novel host for the community of resident parasitoids of Drosophila. To attain a high parasitization rate on the novel host, the parasitoids have to locate it and accept it in the presence of other Drosophila hosts. We conducted a laboratory choice experiment and a semifield trial to investigate host searching and host preference of the three pupal parasitoid species Trichopria drosophilae (Perkins), Pachycrepoideus vindemmiae (Rondani) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
5
11
1
Order By: Relevance
“…Similarly, mass releases of T. drosophilae in berry crops at Colima and Jalisco, Mexico, reduced SWD populations by 50 to 55% [ 66 ]. Given the contrast between the field findings of the current study and those from both laboratory [ 25 , 31 ] and semi-field [ 59 , 61 ] studies, it is relevant to assess Argentinian population lines of both pupal parasitoids under lab conditions. This would enable a comparative assessment of P. vindemiae and T. anastrephae as biocontrol agents of D. suzukii by determining host preference, regulating offered host densities, and analyzing the interspecific competition.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, mass releases of T. drosophilae in berry crops at Colima and Jalisco, Mexico, reduced SWD populations by 50 to 55% [ 66 ]. Given the contrast between the field findings of the current study and those from both laboratory [ 25 , 31 ] and semi-field [ 59 , 61 ] studies, it is relevant to assess Argentinian population lines of both pupal parasitoids under lab conditions. This would enable a comparative assessment of P. vindemiae and T. anastrephae as biocontrol agents of D. suzukii by determining host preference, regulating offered host densities, and analyzing the interspecific competition.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Daane et al [ 57 ] and Wang et al [ 58 ] pointed to T. drosophilae as a more efficient SWD parasitoid in laboratory tests than other well-known pupal parasitoids, such as P. vindemiae . Likewise, Wolf et al [ 59 ] found in the combined release of T. drosophilae and P. vindemiae under semi-field experiments that almost all the parasitoid offspring that emerged from SWD puparia were T. drosophilae adults, despite the two microhabitats tested: soil and foliage.…”
Section: Discussionmentioning
confidence: 96%
“…For T. drosophilae, the reproductive time is much shorter than their maximal lifespan (Yi et al., 2020). Considering further that this species can lay a high number of eggs already in the first days after emergence (Wolf et al., 2021), a time span that can be sustained by access to fruits for feeding, the value of additional lifespan by providing flowers is probably limited. In contrast, P. vindemmiae is a clearly synovigenic species that matures eggs lifelong (Rossi Stacconi et al., 2017; Wolf et al., 2021), and thus, the benefit from additional lifespan translates directly into progeny production (Schmale et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Considering further that this species can lay a high number of eggs already in the first days after emergence (Wolf et al., 2021), a time span that can be sustained by access to fruits for feeding, the value of additional lifespan by providing flowers is probably limited. In contrast, P. vindemmiae is a clearly synovigenic species that matures eggs lifelong (Rossi Stacconi et al., 2017; Wolf et al., 2021), and thus, the benefit from additional lifespan translates directly into progeny production (Schmale et al., 2001). Furthermore, while food sources from fruits coincide with hosts, time to explore flower food sources has to be diverted from host searching by the parasitoids (Takasu & Lewis, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation